Precautions in disciplinary procedure - Caputto Camarena, Javier; Tamayo Lorenzo, Susana (Avances en Supervisión Educativa, 2020)
Public officials must diligence in the performance of their tasks and this diligence is guaranteed by the disciplinary procedure. Throughout the development of the article it will be seen how the disciplinary procedure guarantees compliance with the duties of public employees. Will be reviewed the principles of the sanctioning power, faults and penalties and their prescription to give way, finally, to the disciplinary procedure, always highlighting the search for balance between guaranteeing a quality public service and a disciplinary procedure respectful of the presumption of innocence and the right of defense.